The landscape of climate change adaptation aspirations in the US non‐profit conservation sector. Issue 12 (1st November 2021) - Skikne, Sarah; Cross, Molly; Press, Daniel; Zavaleta, Erika
Abstract: Despite extensive recommendations for adapting conservation to climate change, limited knowledge exists about how practitioners aim to respond. To address this gap, we analyzed proposals for on‐the‐ground climate adaptation projects submitted by US conservation non‐profits, which play a central role in conserving biodiversity. We assessed 415 proposals submitted between 2011 and 2015 to the Wildlife Conservation Society's Climate Adaptation Fund, a US‐based fund focused solely on adaptation for wildlife and ecosystems. We evaluated the distribution of proposed projects across conservation targets, strategies, and activities, and their geographic alignment with climate impacts. Proposals most often targeted river and riparian ecosystems, fish, and birds. Attention on amphibians and invertebrates was disproportionately low relative to their climate vulnerability. Proposals commonly included efforts to restore previous structures and functions, while relatively few described facilitating change (e.g., supporting future‐adapted species). Proposal density was highest along the Atlantic and Pacific coasts, geographically aligned with non‐profit density and public opinion on climate change. There was no geographic alignment between exposure and proposed responses to five of six climate threats (warming, aridity, wildfire, inland flooding, sea level rise). Our findings identify gaps in adaptation attention, and can enhance strategic resource allocation, targeted capacity building, and adaptation outcomes for conservation. Abstract : To understand how US conservation practitioners aim to respond to climate change, we analyzed 415 proposals for on‐the‐ground climate adaptation projects submitted by conservation non‐profits. Most proposals focused on river and riparian ecosystems, fish, and birds, restoration of previous structure and function, and states on the Atlantic and Pacific coasts. We also identified gaps in practitioners' attention: some taxa were relatively neglected given their climate vulnerability, and there was no geographic alignment between exposure and proposed responses to five of six climate threats we tested.